A medical magnesium alloy composite coating for promoting bone growth and a preparation method thereof and a medical magnesium alloy

By preparing a composite coating of titanium dioxide and zirconia bottom coating and a dandelion-shaped hydroxyapatite surface coating on the surface of magnesium alloy, the problems of corrosion resistance and degradation rate regulation in the medical field are solved, and efficient service and rapid degradation absorption are achieved during the bone healing cycle.

CN119405892BActive Publication Date: 2025-05-02HUA RONG KE CHUANG BIOTECHNOLOGY(TIAN JIN) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510012376.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-05-02
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The application of existing magnesium alloys in the medical field is limited by the poor corrosion resistance and difficult to regulate their degradation rate, which makes it difficult to meet the service needs and the requirements of rapid degradation and absorption during the bone healing cycle.

Method used

A composite coating of the bottom coating and the surface coating are arranged in sequence from the surface of the magnesium alloy. The bottom coating contains titanium dioxide and zirconia, and the surface coating is dandelion-shaped hydroxyapatite, which is prepared by magnetron sputtering and hydrothermal reaction methods to control the degradation rate of the magnesium alloy.

Benefits of technology

During the service cycle of magnesium alloy, it improves its corrosion resistance, inhibits degradation, and promotes bone healing; after the service cycle is over, the degradation and absorption of magnesium alloys are accelerated to achieve effective regulation of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405892B_ABST
    Figure CN119405892B_ABST
Patent Text Reader

Abstract

The present invention relates to a medical magnesium alloy composite coating for promoting bone growth, a preparation method thereof and a medical magnesium alloy, wherein the medical magnesium alloy composite coating comprises a bottom coating and a surface coating which are sequentially stacked from the surface of the magnesium alloy outward; the bottom coating comprises titanium dioxide and zirconium oxide; and the surface coating comprises dandelion-shaped hydroxyapatite. The composite coating provided by the present invention can improve the corrosion resistance of the magnesium alloy during the service cycle, inhibit the degradation of the magnesium alloy, and accelerate the degradation of the magnesium alloy after the service cycle, thereby achieving the effect of effectively promoting bone healing and growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a medical magnesium alloy composite coating for promoting bone growth, a preparation method thereof, and a medical magnesium alloy. Background Art

[0002] Magnesium is one of the essential elements for the human body. Magnesium alloys have broad application prospects in the medical field and have good biocompatibility and metabolic mechanisms. However, the corrosion resistance of magnesium alloys is poor and they degrade too quickly, which limits their widespread application as biomedical materials. Although the corrosion resistance of magnesium alloys has been continuously improved by alloying, controlling impurity content and improving processing technology, these improvement measures have limited room for improvement and are still difficult to meet the needs of direct use in many application scenarios. Therefore, it is particularly necessary to modify and modify the surface of magnesium alloys. Surface modification or modification can effectively improve the corrosion resistance of magnesium alloys, which has become the main direction of current research on the application of magnesium alloys.

[0003] At present, there are many types of magnesium alloy surface modification technologies, and the main factors considered include biocompatibility, degradation rate, and effectiveness of inhibiting magnesium alloy degradation. Among them, the research results on the degradation rate of magnesium alloys are mainly to inhibit the degradation of magnesium alloys, and there is a lack of effective control means for the reasonable regulation of the degradation rate. Specifically: during the bone healing cycle, magnesium alloys are generally required to maintain a low degradation rate to fully guarantee the service cycle of magnesium alloys and promote the healing of bone injuries; and after the service of magnesium alloys ends, magnesium alloys are generally required to be rapidly degraded and absorbed.

[0004] Therefore, how to ensure the corrosion resistance of magnesium alloys during their service life while reasonably regulating their degradation rate is a technical problem that needs to be solved in this field. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a medical magnesium alloy composite coating that promotes bone growth, a preparation method thereof, and a medical magnesium alloy. Compared with the prior art, the composite coating provided by the present invention can improve the corrosion resistance of the magnesium alloy during the service cycle, inhibit the degradation of the magnesium alloy, and accelerate the degradation of the magnesium alloy after the service cycle, thereby effectively promoting bone healing and growth.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a medical magnesium alloy composite coating for promoting bone growth, wherein the medical magnesium alloy composite coating comprises a bottom coating and a surface coating which are sequentially stacked from the surface of the magnesium alloy outward;

[0008] The bottom coating includes titanium dioxide and zirconium oxide;

[0009] The surface coating includes dandelion-shaped hydroxyapatite.

[0010] In the present invention, the bottom coating contains titanium dioxide and zirconium oxide, which can significantly promote the adhesion, diffusion and differentiation of cells through the synergistic effect of the two, and increase matrix mineralization, with excellent bone integration and biocompatibility; the surface coating is hydroxyapatite on the one hand, which has a unique similarity with the minerals found in natural bones, can promote remineralization and stimulate bone growth, and is a key factor in bone regeneration; on the other hand, the surface coating is dandelion-shaped, with a large specific surface area, which is conducive to the attachment and growth of cells on the coating surface, thereby improving biocompatibility, and the contact area with bone tissue is increased, which is conducive to the adhesion, proliferation and differentiation of cells, promotes the repair and regeneration of bone tissue, accelerates the bone healing speed, and improves the quality of bone healing. In summary, the composite coating provided by the present invention can effectively improve the bone healing effect and promote bone growth through the synergistic effect of the bottom coating and the surface coating.

[0011] It is worth noting that the composite coating provided by the present invention promotes bone injury healing through the mutual cooperation of the bottom coating and the surface coating, thereby inhibiting the degradation of the magnesium alloy during the service stage and improving the corrosion resistance; on the other hand, after the service of the magnesium alloy ends, galvanic corrosion due to the potential difference is formed between the magnesium alloy substrate and the bottom coating starting from the damage of the surface coating, which accelerates the degradation of the magnesium alloy substrate, causing the magnesium alloy substrate to be rapidly degraded and absorbed, thereby achieving the effect of regulating degradation.

[0012] Preferably, the ratio of the thickness of the surface coating to the thickness of the bottom coating is (200-450):1, for example, it can be 200:1, 220:1, 240:1, 260:1, 280:1, 300:1, 320:1, 340:1, 360:1, 380:1, 400:1, 420:1, 440:1 or 450:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] In the present invention, by preferably controlling the ratio of the thickness of the surface coating to the thickness of the bottom coating, especially controlling the thickness of the bottom coating, the degradation rate can be further regulated. Generally speaking, the thinner the bottom coating is, the earlier the degradation rate peak in the accelerated degradation stage will appear along the time axis, further shortening the overall degradation time, and the thicker the bottom coating is, the vice versa.

[0014] In a second aspect, the present invention provides a method for preparing the medical magnesium alloy composite coating for promoting bone growth according to the first aspect of the present invention, the preparation method comprising the following steps:

[0015] (1) Titanium dioxide and zirconium oxide are deposited on the surface of a magnesium alloy substrate by magnetron sputtering to obtain a substrate containing a bottom coating;

[0016] (2) Immersing the substrate obtained in step (1) in a calcium-phosphorus aqueous solution for hydrothermal reaction to complete the preparation of the medical magnesium alloy composite coating.

[0017] In the preparation method provided by the present invention, a dense bottom coating is first prepared by magnetron sputtering, which can effectively control the composition of the surface coating, avoid the introduction of other components and impurities, avoid damage to the bottom coating during the preparation process, achieve higher corrosion resistance, and make the coating more firm; then, through the hydrothermal reaction method and control the conditions of the hydrothermal reaction, the surface coating is formed under high temperature and high pressure and the crystallization mode of the surface coating is controlled, so that the surface coating has higher firmness and better corrosion resistance, and the effect of regulating the degradation rate "slow at the beginning and fast at the end" is achieved.

[0018] In the present invention, before the magnetron sputtering, the magnesium alloy substrate generally needs to be pretreated to remove surface impurities, such as lipid pollutants and surface oxide film layers. The pretreatment method generally includes physical grinding, cleaning and electrochemical polishing in sequence until the substrate surface is clean. In the preparation method provided by the present invention, the magnetron sputtering method can be used to maintain good integrity of the bottom coating when a large friction force is formed on the substrate surface, and the quality of the bottom coating is further conducive to the adhesion of the surface coating, so that the surface coating is attached to the surface of the bottom coating, thereby ensuring the corrosion resistance of the composite coating.

[0019] In the present invention, the magnesium alloy matrix can be any magnesium alloy commonly used in the art, for example, it can be any one of AE series alloys, AS series alloys, WE series alloys, AZ series alloys, AM series alloys, ZK series alloys, ZM series alloys, Mg-Li series alloys or Mg-Ca series alloys, or a combination of at least two of them, preferably a series of magnesium alloys containing magnesium, zinc and manganese.

[0020] Preferably, in step (1), the magnetron sputtering chamber is evacuated before the magnetron sputtering; the vacuum degree at the end of the evacuation is ≤10 -4 Pa, for example, can be 10 -4 Pa, 10 -5 Pa or 10 6 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In the present invention, the vacuum treatment can be carried out in a conventional manner in the art, generally comprising: firstly sealing the magnetron sputtering chamber, introducing argon gas and evacuating the chamber until the vacuum degree reaches 10 -2 Pa, stop the argon gas and continue to evacuate until the final vacuum degree is ≤10 -4 Pa was then subjected to magnetron sputtering.

[0022] Preferably, the magnetron sputtering process in step (1) comprises: magnetron sputtering using a mixed target of titanium dioxide and zirconium oxide, and sputtering for 15-60 minutes under the conditions of a chamber temperature of 150-200°C and a glow discharge power of 55-65W; wherein the chamber temperature may be, for example, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the glow discharge power may be, for example, 55W, 56W, 58W, 60W, 62W, 64W or 65W, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the sputtering time may be, for example, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] In the present invention, the mass ratio of titanium dioxide to zirconium oxide in the titanium dioxide and zirconium oxide mixed target is generally (60-80):(40-20), preferably 70:30.

[0024] Preferably, the hydrothermal reaction process in step (2) comprises: immersing the substrate in a calcium phosphate aqueous solution, and placing the calcium phosphate aqueous solution in a sealed cavity for hydrothermal reaction.

[0025] Preferably, the calcium-phosphate aqueous solution in step (2) is prepared by a calcium source, a phosphorus source and water; the calcium source comprises dicalcium ethylenediaminetetraacetate, with a molecular formula of C 10 H 12 Ca2N2O8; the phosphorus source includes potassium dihydrogen phosphate; the concentration of the calcium source in the calcium-phosphate aqueous solution is 95-115 g / L, for example, it can be 95 g / L, 96 g / L, 98 g / L, 100 g / L, 102 g / L, 104 g / L, 106 g / L, 108 g / L, 110 g / L, 112 g / L or 115 g / L, but is not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable; the concentration of the phosphorus source in the calcium-phosphate aqueous solution is 25-35 g / L, for example, it can be 25 g / L, 26 g / L, 28 g / L, 30 g / L, 32 g / L, 34 g / L or 35 g / L, but is not limited to the listed values, and other values ​​not listed in the numerical range are equally applicable.

[0026] In the present invention, the molar ratio of calcium to phosphorus in the calcium-phosphate aqueous solution is (1.0-1.7):1, for example, it can be 1.00:1, 1.05:1, 1.10:1, 1.15:1, 1.20:1, 1.25:1, 1.35:1, 1.40:1, 1.45:1, 1.50:1, 1.53:1, 1.60:1 or 1.70:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0027] In the present invention, by preferably controlling the composition and concentration of the calcium-phosphorus aqueous solution, not only the calcium-phosphorus ratio can be controlled to form hydroxyapatite, but also the crystallization mode and orientation can be controlled, thereby controlling the surface coating to be dandelion-shaped.

[0028] Preferably, in step (2), alkali is further added to the calcium phosphate aqueous solution to adjust the pH value; the end point pH value of the pH adjustment is 8-10, for example, it can be 8, 8.5, 9, 9.5 or 10, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] In the present invention, by preferably controlling the endpoint pH value within a specific range, on the one hand, it is possible to avoid that when the pH value is too high, the crystallization rate in the coating preparation is too fast, the crystallization mode is more inclined to dandelion-shaped hydroxyapatite crystals, the porosity of the coating is large, the pore size is too large, and the corrosion resistance is reduced; on the other hand, it is possible to avoid that when the pH value is too low, the crystallization rate in the coating preparation is too slow, the crystallization mode is more inclined to plate-like calcium phosphate, resulting in poor density and firmness of the coating, and further poor corrosion resistance. In the present invention, the alkali can be any commonly used alkali agent in the art, for example, it can be sodium hydroxide.

[0030] Preferably, the temperature of the hydrothermal reaction in step (2) is 100-130°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the pressure of the hydrothermal reaction is the saturated vapor pressure of the calcium phosphate aqueous solution; the time of the hydrothermal reaction is 20-30h, for example, it can be 20h, 22h, 24h, 26h, 28h or 30h, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0031] In the present invention, the pressure of the hydrothermal reaction is the saturated vapor pressure of the calcium phosphate aqueous solution, which is generally ≤3MPa. In the present invention, the morphology of the hydroxyapatite crystals is mainly determined by the composition, temperature and time of the solution.

[0032] Among them, the present invention preferably controls the temperature of the hydrothermal reaction, which can control the crystallization rate and crystallinity of the surface coating. On the one hand, it can avoid that the temperature is too low, resulting in weak intermolecular interaction forces, low crystallization rate and crystallinity, low efficiency of forming the coating, and poor crystallization quality; on the other hand, it can avoid that the temperature is too high, resulting in a faster molecular activity rate, the crystallization process is difficult to control, and the intermolecular interaction force is weakened, resulting in a decrease in crystallinity, forming a loose and unstable coating. In the present invention, the temperature and time of the hydrothermal reaction cooperate with each other, and the time needs to be adjusted in combination with the temperature, which mainly affects the thickness of the coating. On the one hand, it is avoided that the time of the hydrothermal reaction is too short, resulting in the coating being unable to be completely covered, the thickness is too thin or the uniformity is poor, and further resulting in poor corrosion resistance; on the other hand, it is avoided that the time of the hydrothermal reaction is too long, resulting in a too thick coating, the bonding force decreases under the action of external forces, and it is easy to break, which further leads to poor corrosion resistance.

[0033] In a third aspect, the present invention provides a medical magnesium alloy for promoting bone growth, wherein the surface of the medical magnesium alloy contains the medical magnesium alloy composite coating for promoting bone growth as described in the first aspect of the present invention.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The bottom coating of the composite coating provided by the present invention contains titanium dioxide and zirconium oxide, which can significantly promote the adhesion, diffusion and differentiation of cells and increase matrix mineralization, and has excellent bone integration and biocompatibility; the surface coating is dandelion-shaped hydroxyapatite, which has excellent electrochemical properties and improves the corrosion resistance of the magnesium alloy substrate. The dandelion-shaped micro-nano structure can increase the contact area with bone tissue, which is beneficial to the attachment, growth and differentiation of bone cells. The bioactive ions in the coating can stimulate the regeneration and repair of bone tissue, improve the efficiency of bone healing, and make the service life of the product meet the needs of bone healing.

[0036] (2) The composite coating provided by the present invention promotes bone injury healing through the cooperation between the bottom coating and the surface coating, thereby inhibiting the degradation of the magnesium alloy during the service stage and improving the corrosion resistance. On the other hand, after the service of the magnesium alloy ends, galvanic corrosion due to the potential difference is formed between the magnesium alloy substrate and the bottom coating, which accelerates the degradation of the magnesium alloy substrate, causing the magnesium alloy substrate to be rapidly degraded and absorbed, thereby achieving the effect of regulating degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a morphology image of the bottom coating obtained in Example 1 of the present invention;

[0038] Figure 2 is a morphology diagram of the surface coating obtained in Example 1 of the present invention;

[0039] Figure 3is a topographical image of the bottom coating obtained in Example 5 of the present invention;

[0040] Figure 4 is a morphology diagram of the surface coating obtained in Example 5 of the present invention;

[0041] Figure 5 1 is a graph showing the corrosion resistance test results of Example 1, Comparative Example 1 and Comparative Example 3 of the present invention;

[0042] Figure 6 It is a graph showing the test results of the degradation experiments of Example 1, Comparative Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0044] Example 1

[0045] The present embodiment provides a medical magnesium alloy composite coating for promoting bone growth, wherein the medical magnesium alloy composite coating comprises a bottom coating and a surface coating which are stacked in sequence from the surface of the magnesium alloy outward, wherein the bottom coating comprises titanium dioxide and zirconium oxide, and the surface coating comprises dandelion-shaped hydroxyapatite, and the ratio of the thickness of the surface coating to the thickness of the bottom coating is 300:1.

[0046] This embodiment also provides a method for preparing the above-mentioned medical magnesium alloy composite coating, and the preparation method comprises the following steps:

[0047] (1) The pretreated magnesium alloy substrate (specifically magnesium-zinc-manganese alloy) is suspended in the sample fixture position. The sample can be rotated during the preparation process to ensure the uniformity of the coating. The target material is fixed and vacuum treatment is performed, including: closing the chamber cover, turning on the argon gas, and vacuuming to 10 -2 Pa, turn off the argon gas and continue to evacuate to 10 -4 When the temperature reaches 0.040°C, sputtering is started, including: magnetron sputtering is performed using a mixed target of titanium dioxide and zirconium oxide (the mass ratio of titanium dioxide and zirconium oxide is 70:30), and sputtering is performed for 30 minutes under the conditions of a chamber temperature of 180°C and a glow discharge power of 60W to obtain a substrate containing a bottom coating. The morphology of the bottom coating is shown in FIG. Figure 1 As shown;

[0048] (2) The substrate obtained in step (1) is immersed in a calcium phosphate aqueous solution, the calcium phosphate aqueous solution is placed in a sealed cavity, and a hydrothermal reaction is performed at 110° C. for 24 hours, wherein the concentration of dicalcium ethylenediaminetetraacetate in the calcium phosphate aqueous solution is 100 g / L, and the concentration of potassium dihydrogen phosphate is 30 g / L, and sodium hydroxide is added to adjust the pH value to 9, the substrate is taken out and cooled, and then rinsed in pure water and dried to complete the preparation of the medical magnesium alloy composite coating. The morphology of the surface coating is as shown in FIG. Figure 2 shown.

[0049] This embodiment also provides a medical magnesium alloy, wherein the medical magnesium alloy contains the medical magnesium alloy composite coating provided in this embodiment.

[0050] Example 2

[0051] The present embodiment provides a medical magnesium alloy composite coating for promoting bone growth, wherein the medical magnesium alloy composite coating comprises a bottom coating and a surface coating which are stacked in sequence from the surface of the magnesium alloy outward, wherein the bottom coating comprises titanium dioxide and zirconium oxide, and the surface coating comprises dandelion-shaped hydroxyapatite, and the ratio of the thickness of the surface coating to the thickness of the bottom coating is 200:1.

[0052] This embodiment also provides a method for preparing the above-mentioned medical magnesium alloy composite coating, and the preparation method comprises the following steps:

[0053] (1) The pretreated magnesium alloy substrate (same as in Example 1) is suspended in the sample fixture position. The sample can be rotated during the preparation process to ensure the uniformity of the coating. The target material is fixed and vacuum treatment is performed, including: closing the chamber cover, turning on the argon gas, and vacuuming to 10 -2 Pa, turn off the argon gas and continue to evacuate to 10 -4 Pa, sputtering was started, including: magnetron sputtering was performed using a mixed target of titanium dioxide and zirconium oxide (the mass ratio of titanium dioxide to zirconium oxide was 70:30), and sputtering was performed for 45 minutes under the conditions of a chamber temperature of 150°C and a glow discharge power of 65W to obtain a substrate containing a bottom coating;

[0054] (2) Immersing the substrate obtained in step (1) in a calcium phosphate aqueous solution, placing the calcium phosphate aqueous solution in a sealed cavity, and performing a hydrothermal reaction at 100° C. for 30 hours, wherein the concentration of dicalcium ethylenediaminetetraacetate in the calcium phosphate aqueous solution is 95 g / L, and the concentration of potassium dihydrogen phosphate is 35 g / L, and sodium hydroxide is added to adjust the pH value to 8, taking out the substrate and cooling it, then rinsing it in pure water and drying it, thereby completing the preparation of the medical magnesium alloy composite coating.

[0055] This embodiment also provides a medical magnesium alloy, wherein the medical magnesium alloy contains the medical magnesium alloy composite coating provided in this embodiment.

[0056] Example 3

[0057] The present embodiment provides a medical magnesium alloy composite coating for promoting bone growth, wherein the medical magnesium alloy composite coating comprises a bottom coating and a surface coating which are sequentially stacked from the surface of the magnesium alloy outward, wherein the bottom coating comprises titanium dioxide and zirconium oxide, and the surface coating comprises dandelion-shaped hydroxyapatite, and the ratio of the thickness of the surface coating to the thickness of the bottom coating is 450:1.

[0058] This embodiment also provides a method for preparing the above-mentioned medical magnesium alloy composite coating, and the preparation method comprises the following steps:

[0059] (1) The pretreated magnesium alloy substrate (same as in Example 1) is suspended in the sample fixture position. The sample can be rotated during the preparation process to ensure the uniformity of the coating. The target material is fixed and vacuum treatment is performed, including: closing the chamber cover, turning on the argon gas, and vacuuming to 10 -2 Pa, turn off the argon gas and continue to evacuate to 10 -4 Pa, sputtering was started, including: magnetron sputtering was performed using a mixed target of titanium dioxide and zirconium oxide (the mass ratio of titanium dioxide to zirconium oxide was 70:30), and sputtering was performed for 15 minutes under the conditions of a chamber temperature of 200°C and a glow discharge power of 55W to obtain a substrate containing a bottom coating;

[0060] (2) Immersing the substrate obtained in step (1) in a calcium phosphate aqueous solution, placing the calcium phosphate aqueous solution in a sealed cavity, and performing a hydrothermal reaction at 130° C. for 20 hours, wherein the concentration of dicalcium ethylenediaminetetraacetate in the calcium phosphate aqueous solution is 115 g / L, and the concentration of potassium dihydrogen phosphate is 25 g / L, and sodium hydroxide is added to adjust the pH value to 10, taking out the substrate and cooling it, then rinsing it in pure water and drying it, thereby completing the preparation of the medical magnesium alloy composite coating.

[0061] This embodiment also provides a medical magnesium alloy, wherein the medical magnesium alloy contains the medical magnesium alloy composite coating provided in this embodiment.

[0062] Example 4

[0063] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference compared with Example 1 is that the magnetron sputtering time is too short, which is 10 minutes.

[0064] Example 5

[0065] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference compared with Example 1 is that the magnetron sputtering time is too long, which is 90 minutes.

[0066] The morphologies of the bottom coating and the surface coating obtained in this example are as follows: Figure 3 and Figure 4 As shown, from Figure 3 It can be seen that large particles aggregate locally in the bottom coating, which deteriorates the quality of the bottom coating. Under the influence of the deterioration of the quality of the bottom coating, the dandelion-shaped hydroxyapatite coating does not appear on the local surface of the bottom coating where large particles appear, resulting in poor corrosion resistance.

[0067] Example 6

[0068] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference compared with Example 1 is that dicalcium ethylenediaminetetraacetate is replaced by calcium nitrate tetrahydrate in an equal molar amount of calcium ions.

[0069] Example 7

[0070] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference from the embodiment 1 is that the temperature of the hydrothermal reaction is 90°C.

[0071] Example 8

[0072] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference from Example 1 is that the temperature of the hydrothermal reaction is 150°C.

[0073] Example 9

[0074] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference compared with Example 1 is that the hydrothermal reaction time is 15 hours.

[0075] Example 10

[0076] This embodiment provides a method for preparing a medical magnesium alloy composite coating that promotes bone growth. The only difference compared with Example 1 is that the hydrothermal reaction time is 35 hours.

[0077] Comparative Example 1

[0078] This comparative example provides a method for preparing a medical magnesium alloy coating. The only difference from Example 1 is that only step (1) is performed. The composition of the medical magnesium alloy coating is the same as that of the bottom coating in Example 1.

[0079] Comparative Example 2

[0080] This comparative example provides a method for preparing a medical magnesium alloy coating. The only difference from Example 1 is that the magnesium alloy substrate is directly subjected to step (2). The composition of the medical magnesium alloy coating is the same as that of the surface coating in Example 1.

[0081] Comparative Example 3

[0082] This comparative example provides a magnesium alloy substrate. The magnesium alloy substrate provided in this comparative example is the same as that in Example 1, and does not contain a coating on the surface.

[0083] Comparative Example 4

[0084] This comparative example provides a method for preparing a medical magnesium alloy coating. The only difference from Example 1 is that in step (1), a titanium dioxide target is used for sputtering, and the sputtering time is adjusted so that the thickness of the bottom coating remains unchanged, but the component is only titanium dioxide.

[0085] Comparative Example 5

[0086] This comparative example provides a method for preparing a medical magnesium alloy coating. The only difference from Example 1 is that in step (1), a zirconium oxide target is used for sputtering, and the sputtering time is adjusted so that the thickness of the bottom coating remains unchanged, but the component is only zirconium oxide.

[0087] Performance Testing:

[0088] (1) Corrosion resistance test:

[0089] The magnesium alloy substrate obtained in the embodiment and the comparative example was screwed in and out three times with a grade 40 polyurethane material (cortical bone hardness), and then the coating was tested to see if it was intact to reflect the bonding strength between the coating and the magnesium alloy substrate; after the coating was screwed in and out three times, an electrochemical workstation was used to test the corrosion resistance during the service cycle. The reagent used in the electrochemical test was a PBS solution with a pH of 7.4, an initial voltage of -0.3V, an end voltage of 0.3V, a time of 120s, and a Scan Rate of 1mV / s. The results are shown in Table 1.

[0090] Taking Example 1, Comparative Example 1 and Comparative Example 3 as examples, the results of the corrosion resistance test are as follows: Figure 5 As shown, from Figure 5 It can be seen that after three times of screwing in and out, the corrosion resistance of the composite coating is significantly improved compared with the corrosion resistance of the bottom coating and no coating, and it has good corrosion resistance.

[0091] (2) Degradation experimental test: The magnesium alloy matrix is ​​placed in a buffer solvent (PBS solvent) to react and generate hydrogen. The amount of hydrogen is collected and counted to calculate the hydrogen evolution rate of the magnesium alloy matrix. The time of the service stage and the time required for the degradation stage after service are counted, as shown in Table 1.

[0092] Taking Example 1, Comparative Example 1 and Comparative Example 3 as examples, the hydrogen evolution rate of the obtained magnesium alloy matrix within 180 days is as follows: Figure 6 As shown, from Figure 6It can be seen that in Comparative Example 1, there is only a bottom coating, and the hydrogen evolution rate gradually increases from about 15 days to enter the accelerated degradation stage. After reaching a peak value at about 60 days, the hydrogen evolution rate gradually decreases and reaches a relatively stable state; while the composite coating in Example 1 has a low hydrogen evolution rate in the early stage and a good corrosion resistance. The hydrogen evolution rate gradually increases from about 120 days to enter the accelerated degradation stage, and then reaches a peak value at about 160 days, and then gradually decreases to reach a relatively stable degradation rate. Figure 6 It can also be seen that the composite coating provided by the present invention can achieve the effect of regulating the degradation rate "slow at the beginning and fast at the end". Compared with comparative example 3, embodiment 1 can shorten the degradation period by 20-30% as a whole.

[0093] Table 1

[0094]

[0095] In Table 1, “ / ” means that there is no coating on the substrate surface and no coating adhesion test is required.

[0096] From the data in Table 1, we can see the following points:

[0097] (1) From the data of Examples 1-3, it can be seen that the medical magnesium alloy composite coating provided by the present invention has good bonding strength under optimal conditions, good corrosion resistance in the service stage, and can meet the needs of bone healing; the degradation cycle in the degradation stage reaches less than 260 days, with a faster degradation rate, which is conducive to the rapid degradation and absorption of magnesium alloy.

[0098] (2) A comprehensive comparison of the data of Example 1 and Examples 4-5 shows that the present invention further regulates the thickness and quality of the bottom coating by preferentially controlling the sputtering time, and the preparation effect of the bottom coating affects the adhesion of the surface coating and the formation of the dandelion-like morphology, ultimately making the composite coating have good bonding force, and while having good corrosion resistance in the service stage, it forms a good galvanic corrosion effect in the degradation stage, thereby shortening the degradation cycle.

[0099] (3) Comprehensive comparison of the data of Example 1 and Example 6 shows that the present invention can improve the binding force and further improve the corrosion resistance in the service stage by preferably controlling the calcium ethylenediaminetetraacetic acid dicalcium as the calcium source and potassium dihydrogen phosphate as the phosphorus source to control the composition of the calcium-phosphorus aqueous solution, while increasing the degradation rate in the degradation stage, thereby achieving the effect of regulating the degradation rate "slow at the beginning and fast at the end".

[0100] (4) A comprehensive comparison of the data of Example 1 and Examples 7-10 shows that the present invention can regulate the quality and thickness of the surface coating by preferably controlling the temperature and time of the hydrothermal reaction within a specific range, thereby improving the bonding strength of the composite coating, further improving the corrosion resistance during the service stage, and fully ensuring the needs of bone healing.

[0101] (5) Comprehensive comparison of the data of Example 1 and Comparative Examples 1-3 shows that the composite coating provided by the present invention, compared with a single bottom coating or surface coating or no coating, can, on the one hand, ensure the bonding strength with the substrate and ensure good corrosion resistance during the service stage, so that the service cycle meets the needs of bone healing; on the other hand, it can promote the rapid degradation and absorption of magnesium alloy during the degradation stage after bone healing.

[0102] (6) A comprehensive comparison of the data of Example 1 and Comparative Examples 4-5 shows that the bottom coating in the composite coating provided by the present invention can further enhance the corrosion resistance in the service stage and increase the degradation rate in the degradation stage by using the synergistic effect of titanium dioxide and zirconium oxide.

[0103] In summary, the composite coating provided by the present invention can improve the corrosion resistance of the magnesium alloy during the service cycle and inhibit the degradation of the magnesium alloy, and can accelerate the degradation of the magnesium alloy after the service cycle, thereby effectively promoting bone healing and growth.

[0104] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A medical magnesium alloy composite coating for promoting bone growth, characterized in that: The medical magnesium alloy composite coating comprises a bottom coating and a surface coating which are sequentially stacked from the surface of the magnesium alloy outward; The bottom coating includes titanium dioxide and zirconium oxide; The surface coating includes dandelion-shaped hydroxyapatite; The medical magnesium alloy composite coating is obtained by the following preparation method: (1) Using a titanium dioxide and zirconium oxide mixed target for magnetron sputtering, sputtering for 15-60 minutes at a chamber temperature of 150-200°C and a glow discharge power of 55-65W, titanium dioxide and zirconium oxide are deposited on the surface of the magnesium alloy substrate to obtain a substrate containing a bottom coating; (2) immersing the substrate obtained in step (1) in a calcium phosphate aqueous solution for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 100-130° C., the pressure of the hydrothermal reaction is the saturated vapor pressure of the calcium phosphate aqueous solution, and the time of the hydrothermal reaction is 20-30 hours, thereby completing the preparation of the medical magnesium alloy composite coating; The calcium-phosphate aqueous solution is prepared by a calcium source, a phosphorus source and water; the calcium source includes dicalcium ethylenediaminetetraacetate; the phosphorus source includes potassium dihydrogen phosphate; the concentration of the calcium source in the calcium-phosphate aqueous solution is 95-115 g / L; the concentration of the phosphorus source in the calcium-phosphate aqueous solution is 25-35 g / L.

2. The medical magnesium alloy composite coating according to claim 1, characterized in that: The ratio of the thickness of the surface coating to the thickness of the bottom coating is (200-450):

1.

3. A method for preparing a medical magnesium alloy composite coating for promoting bone growth as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) Using a titanium dioxide and zirconium oxide mixed target for magnetron sputtering, sputtering for 15-60 minutes at a chamber temperature of 150-200°C and a glow discharge power of 55-65W, titanium dioxide and zirconium oxide are deposited on the surface of the magnesium alloy substrate to obtain a substrate containing a bottom coating; (2) immersing the substrate obtained in step (1) in a calcium phosphate aqueous solution for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 100-130° C., the pressure of the hydrothermal reaction is the saturated vapor pressure of the calcium phosphate aqueous solution, and the time of the hydrothermal reaction is 20-30 hours, thereby completing the preparation of the medical magnesium alloy composite coating; The calcium-phosphate aqueous solution is prepared by a calcium source, a phosphorus source and water; the calcium source includes dicalcium ethylenediaminetetraacetate; the phosphorus source includes potassium dihydrogen phosphate; the concentration of the calcium source in the calcium-phosphate aqueous solution is 95-115 g / L; the concentration of the phosphorus source in the calcium-phosphate aqueous solution is 25-35 g / L.

4. The preparation method according to claim 3, characterized in that: Before the magnetron sputtering in step (1), the magnetron sputtering chamber is evacuated; The vacuum degree at the end of the vacuum treatment is ≤10 -4 Pa.

5. The preparation method according to claim 3, characterized in that: The hydrothermal reaction process of step (2) comprises: immersing the substrate in a calcium phosphate aqueous solution, and placing the calcium phosphate aqueous solution in a sealed cavity for hydrothermal reaction.

6. The preparation method according to claim 3, characterized in that: In step (2), alkali is also added to the calcium phosphate aqueous solution to adjust the pH value; The end point pH value of the pH adjustment is 8-10.

7. A medical magnesium alloy for promoting bone growth, characterized in that: The surface of the medical magnesium alloy contains the medical magnesium alloy composite coating for promoting bone growth according to claim 1 or 2.

Citation Information

Patent Citations

  • Acicular hydroxyapatite micro-nanostructure coating on magnesium alloy surface and preparation method thereof

    CN109758605A

  • Medical magnesium alloy surface magnesium fluoride / hydroxyapatite composite coating and preparation method thereof

    CN118773610A

  • Medical device for bone implant and method for producing such a device

    US20180321583A1